The effect of combination oral contraceptives on smoking-related symptomatology during short-term smoking abstinence. (February 2015) - Hinderaker, Katie; Allen, Alicia M.; Tosun, Nicole; al'Absi, Mustafa; Hatsukami, Dorothy; Allen, Sharon S.
Abstract: Although an estimated 25% of premenopausal smokers report using oral contraceptives (OC), little is known about how OC use may influence smoking cessation. The purpose of this study was to examine the difference in smoking-related symptomatology during acute smoking abstinence between women on a standardized combination OC (Tri-Sprintec ™ ) compared to women not on OCs (no-OC). Participants were women aged 18–40 who smoked ≥ 5 cigarettes/day and reported regular menstrual cycles. Using a controlled cross-over design, participants completed two six-day testing weeks: Low Progesterone Week (LPW; Follicular (F) phase in no-OC or 1st week of pills in OC) and High Progesterone Week (HPW; Luteal (L) phase in no-OC or 3rd week of pills in OC). Each testing week included daily assessment of symptomatology and biochemical confirmation of smoking status. During smoking abstinence, the OC group (n = 14) reported significantly lower levels of positive affect (21.56 ± 7.12 vs. 24.57 ± 6.46; β = 3.63, p = 0.0323) than the no-OC group (n = 28). Further significant interactions between group and testing week were observed as follows: Smoking satisfaction was higher during LPW in the OC group (LPW: 4.29 ± 1.30 vs. HPW: 4.10 ± 1.37) but higher during HPW in the no-OC group (LPW: 3.91 ± 1.30 vs. HPW: 4.23 ± 1.30; β = − 0.5499, p < 0.0001). Similar interactions were noted in negative affect and psychological reward of smoking. These results suggest that women on OCs may have different patterns of smoking-related symptomatology during short-term smoking abstinence as compared to women not on OCs. Additional work is needed to examine how this may affect smoking cessation efforts. Highlights: We compared smoking-related symptomatology in women by oral contraceptive (OC) use. OC users had lower levels of positive affect during smoking cessation. Smoking satisfaction and psychological reward varied by OC use and menstrual cycle. OC users had more menstrual cycle variation in negative affect.